Ethical Responsibility of Neuromarketing Companies in Harnessing the Market Research – a Global Exploratory Approach - Nicolae Al. Pop; Dan-Cristian Dabija; Ana Maria Iorga (Amfiteatru Economic Journal, 2014)
A key challenge in the 21st century is identifying how to satisfy consumers' needs in the best manner possible, whilst ensuring companies' financial profitability. Scientists play a major role in achieving this goal, as research methods, techniques and tools have continuously evolved. In the last two decades, the development of these instruments has seen an important boost, as neuromarketing methods and techniques added depth and accuracy to traditional studies. The main aim of this paper is to highlight the role and importance of neuromarketing research techniques in the evolution of neurosciences and to explain how these techniques are used in market research. One of the most important challenges for companies who offer neuromarketing services is to stick to ethical principles when performing the investigations. This is an obligation they have both towards the beneficiaries – the companies providing products or services – and towards their consumers as well. This challenge has always been a subject of dispute between the advocates and critics of neuromarketing.
Keywords: D87; M30; M31; 330; neuromarketing; neuroscience; market research; ethical responsibility; experimental research